Study on Mechanical Behaviour of Hybrid Composites - Prasad, T.; Chinna Srinivasa Rao, P.; Vijay Kiran, B. (International Journal of Engineering and Technology, 2018)
Composite containing more than one type of fiber is known as hybrid composites. Natural fibers and artificial fibers can be used for fabrication of Hybrid composites. Hybrid composites will give mechanical properties than fiber reinforced composites. The element of fibers in Hybrid composite, the elements of fibers can be changed in different ways leading to variation in its properties. For preparing the hybrid composites using different fibres reinforced with matrix. Hybrid composite has wider applications across industries such as aerospace, automobiles, Marine etc. In this paper, fabrication of hybrid composites is done manually using hand layup method. It is then subjected to a compressive load for thorough distribution of resin in respective lamina. The fabricated composite is tested for its flexural and tensile properties. The result obtained is further analyzed for the study of the material fabricated.